Does Diversity Make a Difference? The Effect of Profile And Diversity of Academics on Innovation Performance of Turkish Universities - ilic, derya; Tatarlar, Ceren Deniz; Turhan, Rasim (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The concept of innovation includes good ideas and smart individuals as accepted by most people. One of the most important driving forces for innovative ideas in organizations is human diversity. Diversity is a broad concept which includes physical characteristics like race, gender and ethnicity and also social and political differences of opinions. In this study, the effect of different specialties of employees on innovation performances has been researched in context of universities. Recognizing the link between diversity, creativity and innovation, the concept of academic entrepreneurship is becoming increasingly important due to the changing role of universities in knowledge-based economies. The research has been conducted by analyzing the academicians’ profiles of first 15 and last 15 universities of the “Index of Entrepreneur and Innovative Universities” which is announced by TUBITAK (Scientific and Technological Research Council of Turkey). This index presents the innovation performances of universities. The academicians’ profiles have been analyzed through their diverse specialties and its relevance with the ranking of the universities. The diversity factors of academicians were determined as gender, title, educational background, overseas experience and work experience as a result of resume database scanning. Obtained data were analyzed in SPSS 15.0 for Windows for presenting the relationship between innovation performance and organizational diversity. As a result, there is a significant relationship between overseas experience, educational background of academics and innovation performances in universities. Key words: Organizational diversity, organizational innovation, innovation performance, academics, academic entrepreneurship, diversity management